2020
DOI: 10.1155/2020/6738348
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Acute Coronary Syndromes in a Patient with Idiopathic Thrombocytopenic Purpura

Abstract: A 53-year-old man was admitted to a peripheral hospital with the diagnosis of acute myocardial infarction without ST elevation. Due to the concomitant presence of first-diagnosed thrombocytopenia (platelet count 50.000/μL), it was decided to be treated conservatively with clopidogrel. Five days later, he developed an acute myocardial infarction with ST elevation (STEMI) and was transferred to our department for primary percutaneous coronary intervention (PCI). Coronary angiography revealed threevessel disease.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In our case, we adopted a stepwise method and were successful in achieving target platelet levels with prednisolone alone and did not result in acute stent thrombosis in the immediate term. Although medical management with single antiplatelet therapy is an option, there is the risk of further ischaemic event and conversion into STEMI, which may further compromise cardiac function and predispose to arrhythmias 6. Therefore, invasive management should be considered if deemed suitable for the patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our case, we adopted a stepwise method and were successful in achieving target platelet levels with prednisolone alone and did not result in acute stent thrombosis in the immediate term. Although medical management with single antiplatelet therapy is an option, there is the risk of further ischaemic event and conversion into STEMI, which may further compromise cardiac function and predispose to arrhythmias 6. Therefore, invasive management should be considered if deemed suitable for the patient.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Al-Lawati et al showed in their case report that obstructive coronary lesions presenting as STEMI in patients with ITP may be successfully treated with OCT-guided plain old balloon angioplasty only 5. Similarly, Iakovis et al opted for a drug-eluting balloon in addition to standard semicompliant balloons 6. These approaches avoid implantation of a stent and therefore DAPT may be stopped earlier than 1 month if needed.…”
Section: Discussionmentioning
confidence: 99%